ICRP Jakarta and Interfaith Marriage Assistance in Indonesia: Civil Rights, Legal Interpretation, and Advocacy for Interfaith Couples - Aris Setiyanto, Danu; Ayu Aryani, Sekar; Wahyuni, Sri (Journal of Islamic Law, 2024)
The Indonesian Constitution guarantees its citizens the freedom to express their fundamental rights. However, in practice, this guarantee faces numerous challenges and exceptions, particularly in the context of interfaith marriages. This article aims to explore the role of the Indonesian Conference on Religion and Peace (ICRP) in Jakarta in addressing the phenomenon of interfaith marriages. This study utilises James C. Scott’s theory of resistance to examine how ICRP Jakarta combats stereotypes and negative stigmas associated with interfaith marriages. Data collection techniques include direct field observations and in-depth interviews with twelve key informants, including ICRP Jakarta officials, religious leaders (Islam, Catholicism, and Buddhism), and interfaith couples utilising ICRP Jakarta’s services. A socio-legal approach is employed to demonstrate ICRP Jakarta’s efforts to accommodate interfaith marriage practices. The study finds that ICRP Jakarta’s resistance involves mainstreaming civil rights discourse, interpreting contradictory legal frameworks, and advocating for interfaith couples through juridical, social, and direct advocacy. This article argues that ICRP Jakarta’s resistance to stereotypes and negative stigmas against interfaith marriages exemplifies how research and practical action can foster positive change in a multicultural society. These findings have implications for shaping a more inclusive and tolerant understanding and policy towards interfaith marriages. [Konstitusi Indonesia menjamin kebebasan warga negara dalam mengekspresikan hak-hak dasar mereka. Namun, dalam praktiknya, jaminan ini menghadapi banyak tantangan dan pengecualian, terutama dalam konteks pernikahan beda agama. Artikel ini bertujuan untuk mengeksplorasi peran Indonesian Conference on Religion and Peace (ICRP) Jakarta dalam menangani fenomena pernikahan beda agama. Dengan menggunakan teori resistensi James C. Scott, artikel ini mengkaji bagaimana ICRP Jakarta melawan stereotip dan stigma negatif terkait pernikahan beda agama. Teknik pengumpulan data mencakup observasi langsung di lapangan dan wawancara mendalam dengan dua belas informan kunci, termasuk pengurus ICRP Jakarta, tokoh agama (Islam, Katolik, dan Buddha), serta pasangan beda agama yang menggunakan layanan ICRP Jakarta. Pendekatan sosio-legal digunakan untuk mendemonstrasikan upaya ICRP Jakarta dalam mengakomodasi praktik pernikahan beda agama. Artikel ini menemukan bahwa resistensi yang dilakukan oleh ICRP Jakarta meliputi pengarusutamaan wacana hak-hak sipil, interpretasi kerangka hukum yang kontradiktif, serta advokasi bagi pasangan beda agama dalam bentuk advokasi yuridis, sosial, dan langsung. Artikel ini berargumen bahwa resistensi ICRP Jakarta terhadap stereotip dan stigma negatif terhadap pernikahan beda agama menunjukkan bagaimana penelitian dan aksi nyata dapat berjalan beriringan untuk menciptakan perubahan positif dalam masyarakat yang multikultural. Temuan ini berimplikasi pada pembentukan pemahaman dan kebijakan yang lebih inklusif dan toleran terhadap fenomena pernikahan beda agama.]